METHODS FOR ENSURING ENVIRONMENTAL SAFETY OF CITIES - Plugotarenko, N. K.; Gusakova, N. V.; Dolgopolova, A. G. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2018)
Currently, the environmental situation of urban environment can have an impact on human health and social comfort of population. This paper is devoted to the search for ways to ensure the environmental safety of cities. To improve the ecological situation, the authors propose the way to form the ecological framework of the city. The principles of formation of environmentally safe situation are considered. A logical-probabilistic model is proposed for assessing the environmental safety of cities.